2009
DOI: 10.1093/toxsci/kfp297
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Investigation on the Metabolism of 1,3-Butadiene and of Its Oxidized Metabolites in Once-through Perfused Livers of Mice and Rats

Abstract: The industrial chemical 1,3-butadiene (BD) is a potent carcinogen in mice and a weak one in rats. This difference is generally related to species-specific burdens by the metabolites 1,2-epoxy-3-butene (EB), 1,2:3,4-diepoxybutane (DEB), and 3,4-epoxy-1,2-butanediol (EBD), which are all formed in the liver. Only limited data exist on BD metabolism in the rodent liver. Therefore, metabolism of BD, its epoxides, and the intermediate 3-butene-1,2-diol (B-diol) was studied in once-through perfused livers of male B6C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…BD is chemically inert, but is metabolized to several electrophilic epoxides that are capable of alkylating cellular macromolecules, to which the genotoxic and carcinogenic effects of BD are attributed (see Section 2.3 below). The metabolism of BD to reactive epoxide metabolites, including 2,3-epoxy-1-butene (EB), 1,2,3,4-diepoxybutane (DEB), and 3,4epoxybutane-1,2-diol (EBD), has been well studied in mice, rats, and humans (as reviewed in Himmelstein et al [16], Albertini et al [17], Kirman et al [18], Filser et al [19], which indicates that the metabolic pathways for BD are qualitatively similar, but exhibit large quantitative differences across species. Internal doses of these metabolites reflect pathways accounting for their formation (e.g., oxidation) as well as their clearance (e.g., hydrolysis, conjugation) as depicted in Figure 1.…”
Section: Metabolism Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…BD is chemically inert, but is metabolized to several electrophilic epoxides that are capable of alkylating cellular macromolecules, to which the genotoxic and carcinogenic effects of BD are attributed (see Section 2.3 below). The metabolism of BD to reactive epoxide metabolites, including 2,3-epoxy-1-butene (EB), 1,2,3,4-diepoxybutane (DEB), and 3,4epoxybutane-1,2-diol (EBD), has been well studied in mice, rats, and humans (as reviewed in Himmelstein et al [16], Albertini et al [17], Kirman et al [18], Filser et al [19], which indicates that the metabolic pathways for BD are qualitatively similar, but exhibit large quantitative differences across species. Internal doses of these metabolites reflect pathways accounting for their formation (e.g., oxidation) as well as their clearance (e.g., hydrolysis, conjugation) as depicted in Figure 1.…”
Section: Metabolism Overviewmentioning
confidence: 99%
“…In the effluent of mouse livers perfused with BD, all three epoxides (EB, DEB, and EBD) and BD-diol were observed, while in effluents from rat livers perfused with BD, only EB and BD-diol were detected. When the mouse and rat livers were perfused with EB, Filser et al [ 19 , 26 ] found that BD-diol, EBD, and DEB were formed, with BD-diol predominating in both species. DEB formation was greater in mouse than in rat livers [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation